Transesterifikasi In Situ Minyak Biji Pepaya Menggunakan Ko-pelarut Tetrahidrofuran: Pengaruh Waktu Reaksi dan Penggunaan Katalis Natrium Hidroksida - Elvianto Dwi Daryono; Muyassaroh; Hudha, Mohammad (Talenta Publisher (Universitas Sumatera Utara), 2024)
The papaya seed oil is a non-food oil that can be used as raw material for biodiesel. The transesterification process using oil as raw material requires long process stages so it is not efficient. In situ transesterification with a co-solvent is an alternative to overcome this problem. This research aims to obtain optimum conditions for the in situ transesterification reaction of papaya seed oil with THF co-solvent. The research operating conditions included stirring speed 450 rpm, reaction at room temperature, oil:methanol molar ratio = 1:101.39, catalyst:oil molar ratio = 0.5:1, oil:THF molar ratio = 1: 67.85, reaction time are 3, 8, 13, 18, 23, 28 minutes and reactions with and without a NaOH catalyst. The best research conditions were obtained in the in situ transesterification reaction of papaya seed oil with THF co-solvent using a NaOH catalyst at a reaction time of 33 minutes, producing a crude yield of 74.38% and methyl esters concentration of 98,036.4 ppm and physical properties of biodiesel that met SNI 7182-2015, namely density 0.89 g/mL and acid number 0.44 mg KOH/g sample.